Perspectives on the Genomics of HSP Beyond Mendelian Inheritance - Bis-Brewer, Dana M.; Züchner, Stephan (Frontiers in Neurology, 2018)
Hereditary Spastic Paraplegia is an extraordinarily heterogeneous disease caused by over 50 Mendelian genes. Recent applications of next-generation sequencing, large scale data analysis, and data sharing/matchmaking, have discovered a quickly expanding set of additional HSP genes. Since most recently discovered HSP genes are rare causes of the disease, there is a growing concern of a persisting diagnostic gap, estimated at 30-40%, and even higher for sporadic cases. This missing heritability may not be fully closed by classic Mendelian mutations in protein coding genes. Here we show strategies and published examples of broadening areas of attention for Mendelian and non-Mendelian causes of HSP. We suggest a more inclusive perspective on the potential final architecture of HSP genomics. Efforts to narrow the heritability gap will ultimately lead to more precise and comprehensive genetic diagnoses, which is the starting point for emerging, highly specific gene therapies.